2020
DOI: 10.1039/d0fo01162b
|View full text |Cite
|
Sign up to set email alerts
|

Ficus caricapolysaccharide attenuates DSS-induced ulcerative colitis in C57BL/6 mice

Abstract: FCPS effectively alleviates DSS-induced colitis, possibly via its beneficial effects on reshaping the gut microbiome and enhancing the formation of SCFAs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(46 citation statements)
references
References 68 publications
1
43
0
Order By: Relevance
“…During the last twenty years, multiple publications identified a changed composition and metabolism of the gut microbiota associated with increased SCFA concentrations as a possible anti-inflammatory mechanism [ 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 ]. In contrast, high-sugar diet was shown to enhance susceptibility to DSS-colitis via depletion of luminal short chain fatty acids [ 181 ].…”
Section: Short Chain Fatty Acidsmentioning
confidence: 99%
“…During the last twenty years, multiple publications identified a changed composition and metabolism of the gut microbiota associated with increased SCFA concentrations as a possible anti-inflammatory mechanism [ 173 , 174 , 175 , 176 , 177 , 178 , 179 , 180 ]. In contrast, high-sugar diet was shown to enhance susceptibility to DSS-colitis via depletion of luminal short chain fatty acids [ 181 ].…”
Section: Short Chain Fatty Acidsmentioning
confidence: 99%
“…The mucosal biopsy of IBD patients and the acetic acid-induced rat colitis model also con rmed that the expression level of TNF-α was positively correlated with the degree of colitis [32]. TNF-α could trigger the phosphorylation of myosin light chain, destroy the intestinal barrier and tight junction proteins, and can up-regulate the expression of iNOS and COX-2, activate the NF-κB pathway and other in ammatory signals, and initiate the cascade of in ammation reaction, thus resulting in sustained damage to the intestinal mucosa [2]. COX-2 catalyzes the release of many kinds of PGs (such as PGE4) and leukotrienes by arachidonic acid 33].…”
Section: Ento-pb Regulated the Expression Of In Ammatory Cytokines Inmentioning
confidence: 86%
“…Many evidences indicated that cytokines TNF-α and IL-1β play important roles in intestinal in ammation and barrier dysfunction [31]. Elevated levels of TNF-α and IL-1β increase neutrophil in ltration, damage the intestinal barrier, and drive diarrhea symptoms of UC [2]. The mucosal biopsy of IBD patients and the acetic acid-induced rat colitis model also con rmed that the expression level of TNF-α was positively correlated with the degree of colitis [32].…”
Section: Ento-pb Regulated the Expression Of In Ammatory Cytokines Inmentioning
confidence: 93%
See 2 more Smart Citations